2013
DOI: 10.1007/s00234-013-1224-z
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial treatment of direct carotico-cavernous fistulas with coils and Onyx

Abstract: The adjuvant use of Onyx with detachable coils in direct CCF through the arterial route is a safe and effective method for embolization with immediate and complete occlusion of the fistula. To the best of our knowledge, this is the first case series of demonstration of arterial use of Onyx with coils in the treatment of direct CCFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…For indirect fistulas, with small and/or multiple fistulous points, we used Onyx-18, an ethylene-vinyl alcohol copolymer mixed with tantalum powder. We achieved a 62.5% success rate with Onyx-18, which is comparable to other reports [9,14,15,18,19], but inferior to coil embolisation, partly because we assumed those fistulas that we failed to microcatheterise and were bound to be treated with Onyx-18 were marked as failures in our calculations. Other authors used the technique successfully [15,18,19].…”
Section: Discussionsupporting
confidence: 85%
“…For indirect fistulas, with small and/or multiple fistulous points, we used Onyx-18, an ethylene-vinyl alcohol copolymer mixed with tantalum powder. We achieved a 62.5% success rate with Onyx-18, which is comparable to other reports [9,14,15,18,19], but inferior to coil embolisation, partly because we assumed those fistulas that we failed to microcatheterise and were bound to be treated with Onyx-18 were marked as failures in our calculations. Other authors used the technique successfully [15,18,19].…”
Section: Discussionsupporting
confidence: 85%
“…15) The usefulness of liquid embolizing substances, such as Etylene vinyl oxide copolymer (Onyx) (eV3 Covidien, Irvine, CA, USA) and N-butyl-2-cyanoacrylate (NBCA), has been reported, but glue migration-related complications may occur. 16) In some cases in which sinus packing is required, an access to the SOV or cortical outflow tract becomes difficult in the latter half of the procedure regardless of the type of embolizing substance; embolization of the venous outflow tract should be predominantly conducted. In the present case, embolization of the cortical venous outflow tract was single coil through a transvenous approach.…”
Section: Resultsmentioning
confidence: 99%
“…High success rates with endovascular embolization of CC fistulas are reported across the board. [45][46][47][48] Liu et al reported recovery of oculomotor function after initial treatment with detachable balloons in all of 98 patients who presented with oculomotor nerve paresis in the setting of a traumatic CC fistula. 49 Visual impairment also often recovers within the first 2 weeks after endovascular therapy if the fistula is treated early.…”
Section: Carotid Cavernous Fistulasmentioning
confidence: 99%
“…49 Visual impairment also often recovers within the first 2 weeks after endovascular therapy if the fistula is treated early. 46…”
Section: Carotid Cavernous Fistulasmentioning
confidence: 99%